Copyright Content on the YouTube Platform as Collateral for Creative Economy Financing - Azka Adriliya, Putri; Abubakar, Lastuti; Handayani, Tri (Universitas Ekasakti, 2024)
The utilization of technology presents an opportunity for creative economy practitioners to expand their work, one of which is by leveraging digital platforms. The government provides support for creative economy practitioners through the implementation of Government Regulation Number 24 of 2022, which recognizes intellectual property rights as collateral for financing, similar to how copyright content on platforms like YouTube can be used as fiduciary collateral for intangible movable assets. Through this financing scheme, there is potential for content creators to utilize their content as collateral, aiming to secure financing for productivity. This research employs a juridical analysis method to explore the potential of copyright content on the YouTube platform as collateral for financing within the creative economy. The conclusion drawn is that it is indeed feasible to utilize copyright content on the YouTube platform as collateral for financing, in the form of tangible collateral. Valuation, on the other hand, can be based on the number of viewers or income approaches, even though as of now, there isn't a definitive standardization regarding this matter.